Currently Available Strategies for Target Identification of Bioactive Natural Products - Li, Gen; Peng, Xuling; Guo, Yajing; Gong, Shaoxuan; Cao, Shijie; Qiu, Feng (Frontiers in Chemistry, 2021)
In recent years, biologically active natural products have gradually become important agents in the field of drug research and development because of their wide availability and variety. However, the target sites of many natural products are yet to be identified, which is a setback in the pharmaceutical industry and has seriously hindered the translation of research findings of these natural products as viable candidates for new drug exploitation. This review systematically describes the commonly used strategies for target identification via the application of probe and non-probe approaches. The merits and demerits of each method were summarized using recent examples, with the goal of comparing currently available methods and selecting the optimum techniques for identifying the targets of bioactive natural products.